How the fish community structure change with seasons in Zhoushan Fishing Ground, China? - Yuru Li; Chenchen Yan; Peilong Ju; Baogui Liu; Jing Wang; Chang Zhang; Wenchao Zhang; Yingbin Wang; Yingbin Wang (Frontiers in Marine Science)
Understanding seasonal variations in fish communities is important for fishery resources conservation and management in fishery economic zones. However, there are still knowledge gaps regarding to the differential responses of fish functional traits to various disturbances. Here, we sampled fish communities of 20 sites during autumn (November 2023) and spring (April 2024) in Zhoushan Fishing Ground. Taxonomic diversity (TD), functional diversity (FD), and functional redundancy (FR) were calculated to investigate the state of the fish communities and their seasonal changes. Beta diversity was calculated based on the pairwise communities of spring and autumn and decomposed into turnover and nestedness proportions, to investigate the dissimilarities of the fish communities between the two seasons and their drive mechanisms. We also applied R-mode linked to Q-mode (RLQ) and fourth-corner methods to test the relationships between fish functional traits and environmental variables (trait-environment relationships). These results showed that the mean values of taxonomic and functional beta diversities were 0.852 and 0.769, respectively, which indicate that taxonomic and functional structures of the fish communities have high dissimilarities between spring and autumn. However, the taxonomic and functional structures showed different ecological processes of seasonal changes with the former were mainly driven by species turnover (occupied 89.9% of the total dissimilarity) and the latter were driven by both functional turnover and nestedness (occupied 57.9% and 42.1% of the total dissimilarity, respectively). Species occurrence, environmental variables, and functional traits matrices were closely correlated, which mainly result from the significant trait-environmental relationships. Combining with TD, FD, and FR, we concluded that the fish communities in autumn had higher resistance to environmental changes than in spring. Our findings are accepted to serve as a basis for fishery management.